62nd Open Seminar on Acoustics and 91st Seminar of Czech Acoustical Society - OSA 2015, Chronicle (Archives of Acoustics, 2015)
The paper presents the abstracts presented during 62nd Open Seminar on Acoustics and 91st Seminar of Czech Acoustical Society.